The political cartoons in the Binômio newspaper during it’s humoristic phase (1952-1956) - Dias, Maria Regina Álvares Correia; Carneiro, André Matias (InfoDesign, 2022)
The newspaper Binômio, which circulated from 1952 to 1964, was marked by an oppositional personality throughout its trajectory. Thus, this article deals specifically with images signed by collaborating cartoonists, disseminated during the period of humor of the periodical, between 1952 to 1956. The main objective is to recover part of the graphic memory of this newspaper, based on an analysis of the caricature and denunciatory content of works produced by artists at the time. Through investigations in primary sources, bibliographic research and an interview with one of the founders, the results demonstrate that the political cartoon was an essential element in the construction of the Binômio’s critical-humoristic approach in that period.